Estudio de los factores psicosociales caso: Cuerpo de Bomberos del cantón Pujilí. - Segovia Pazmiño, Fabián Marcelo (2021)
Given the importance that human talent management contains in business administration, by raising the satisfaction and productivity of each of the workers, it has been inquiring how psychosocial risk factors intervene in the working day, and how it causes a decline in the performance and motivation, in the workers. In this context, the Fire Department of the Pujilí canton is not exempt from the presence of psychosocial risks, which is why it is necessary to determine the incidence of these in the management of human talent. Being necessary to collect information from secondary sources in order to structure the first chapter and theoretically support the research. Regarding the methodology, the research was qualitative, descriptive, bibliographical and with categories of analysis according to the objectives set in order to describe the psychosocial risks and how to improve the management of human talent by having them controlled. Additionally, information was collected from primary sources that allowed a situational diagnosis to obtain an overview of the problem; In this same information collection phase, 36 members of the fire department of the Pujilí canton were surveyed, applying the ISTAS 21 questionnaire with which the level of exposure to psychosocial risk factors in the institution is identified. The results of the investigation allow us to determine that in effect the staff has a high degree of psychosocial risks, for this reason this investigation is of great importance for the Human Talent Unit of the institution since it determines the guidelines to establish optimal strategies to protect the comprehensive well-being of employees